2008
DOI: 10.1007/s00280-008-0818-3
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center phase II study of S-1 plus paclitaxel as first-line therapy for patients with advanced or recurrent unresectable gastric cancer

Abstract: Purpose This study was conducted to evaluate the safety and eYcacy of S-1 and paclitaxel combination therapy for patients with advanced gastric cancer. Methods Eligible patients had previously untreated advanced or relapsed gastric cancer with measurable lesion(s) and an ECOG PS of 0-2. Treatment consisted of S-1 35 mg/ m 2 p.o. b.i.d. on days 1-14 followed by a 7-day oV plus paclitaxel 70 mg/m 2 i.v. on days 1 and 8 of a 21-day cycle. Results Fifty-six patients (M/F = 37/19) were enrolled. The median age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
3
7
1
Order By: Relevance
“…Unfortunately, there are no data directly comparing the anti-tumor activity of 5-FU plus taxane (paclitaxel or docetaxel) with that of S-1 plus taxane. Although there are limitations in comparing the results of different studies, the efficacy of S-1 plus paclitaxel has been reported in phase II trials with a response rate of 40–55% and a median survival of 9–15 months, and this is comparable to the present data for FLTAX [31,32,33]. Accordingly, the FLTAX regimen may be a good option for GC patients who are not suitable for treatment with platinum agents.…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, there are no data directly comparing the anti-tumor activity of 5-FU plus taxane (paclitaxel or docetaxel) with that of S-1 plus taxane. Although there are limitations in comparing the results of different studies, the efficacy of S-1 plus paclitaxel has been reported in phase II trials with a response rate of 40–55% and a median survival of 9–15 months, and this is comparable to the present data for FLTAX [31,32,33]. Accordingly, the FLTAX regimen may be a good option for GC patients who are not suitable for treatment with platinum agents.…”
Section: Discussionsupporting
confidence: 76%
“…Many phase II studies have also been performed to investigate the safety profi le and effectiveness of weekly paclitaxel-containing combination therapies for advanced and metastatic gastric cancers (Table 4) [ [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Weekly Administration Of Paclitaxelmentioning
confidence: 99%
“…Studies of combinations with oral S-1 (tegafur, gimeracil, oteracil) have also been performed [47,49,[55][56][57][58][59]. In these trials, response rates ranged from 40% to 65% and MSTs ranged from 8.9 to 15.5 months.…”
Section: Weekly Administration Of Paclitaxelmentioning
confidence: 99%
“…Additionally, recent reports indicate that one of the molecular events of apoptosis is activation of the caspases by a signal transduction cascade [10] . Currently, chemotherapy using plant-derived, anti-cancer drugs such as paclitaxel [11] , vinorelbine [12] , or vincristine [13] has been proven to be effective in clinical settings. It was shown that these products enhance cell growth inhibition in different cancer cell lines and are highly effective and safe in clinical trials.…”
Section: Introductionmentioning
confidence: 99%